Solving channel assignment problem for mobile communication with soft computing - Gu, Wen (2008)
In industry, agriculture and economy, we often encounter constrained optimization problems. One common way to deal with these problems is to transform the constrained optimization problems into unconstrained ones by introducing a penalty function, which is controlled by a number of penalty coefficients into the objective function.. However, how to set the penally coefficients turns out to be a difficult problem itself [16]! Stochastic ranking is a novel constraint-handling technique proposed by P.T. Runarsson and Xin Yao. Applying this technique for constrained evolutionary make us do not need to determine the hard-setting penalty coefficients. We demonstrate this novel approach with one difficult combinatorial optimization problem, i.e., the channel assignment problem for cellular mobile communications.